2019
DOI: 10.1159/000500541
|View full text |Cite
|
Sign up to set email alerts
|

Placenta-Specific 8 Is Overexpressed and Regulates Cell Proliferation in Low-Grade Human Pancreatic Neuroendocrine Tumors

Abstract: Background/Aims: Many aspects of the biology of pancreatic neuroendocrine tumors (PanNETs), including determinants of proliferative, invasive, and metastatic potential, remain poorly understood. Placenta-specific 8 (PLAC8), a gene with unknown molecular function, has been reported to have tumor-promoting roles in different human malignancies, including exocrine pancreatic cancer. Since preliminary data suggested deregulation of PLAC8 expression in PanNET, we have performed detailed analyses of PLAC8 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…When Plac8 was depleted in CD8 T cells, we observed a decrease in effector CD8 T cell establishment relative to WT CD8 T cells which led us to hypothesize that Plac8 promotes proliferation within CD8 T cells. This hypothesis is supported by Plac8's documented role in promoting proliferation in multiple cancerous epithelial cell lines [12,26,27]. However, in our model we found that Plac8 does not regulate the proliferation of antigen-specific CD8 T cells as measured by similar surface expression of CD25 and BrdU incorporation 8 dpi (Fig 5E).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…When Plac8 was depleted in CD8 T cells, we observed a decrease in effector CD8 T cell establishment relative to WT CD8 T cells which led us to hypothesize that Plac8 promotes proliferation within CD8 T cells. This hypothesis is supported by Plac8's documented role in promoting proliferation in multiple cancerous epithelial cell lines [12,26,27]. However, in our model we found that Plac8 does not regulate the proliferation of antigen-specific CD8 T cells as measured by similar surface expression of CD25 and BrdU incorporation 8 dpi (Fig 5E).…”
Section: Discussionsupporting
confidence: 73%
“…In other cell types, Plac8 is known to regulate cellular proliferation [ 12 , 26 , 27 ], and modified proliferation can impact CD8 T cells not only acutely during the effector phase of the anti-viral response, but also the development of subsequent memory CD8 T cells. Therefore, we next assessed whether Plac8 is important for the establishment of the immunodominant influenza nucleoprotein (NP)-specific CD8 T cells within WT and Plac8 -/- mice.…”
Section: Resultsmentioning
confidence: 99%
“…FASN-KD induces apoptosis and downregulates both p-RPS6 (S240/244) and total (t)-RPS6 through AKT/mTOR/SK6 axis by stimulating protein ubiquitination in ovarian cancer cells [173] Gal-13/PLAC8 (galectin-13/placenta-specific 8) absent in healthy adult exocrine pancreas but ectopically expressed in pancreatic ductal adenocarcinoma [174][175][176] PLAC8-KD downregulates p-RPS6 (S235/236) and p-RB (S807/811) in human BON-1 pancreatic neuroendocrine tumor cells [177] GlnRS/QARS (glutaminyl-tRNA synthase)…”
Section: Upstream Effectors Of Rps6 Phosphorylationmentioning
confidence: 99%
“…Our results showed that compared to normal villi MAPK14, MAPK13, MAPK7 and MAPK1 were significantly down-regulated in PSTT, but Köbel et al have reported that MAPK was highly expressed [38]. PLAC8, also named onzin, is a small protein (∼16 kDa) that was originally described to be highly expressed in mouse placenta [39] and its deficiency in mice may result in innate immunity deficiency [40]. We also found that PLAC8 is highly expressed in PSTT but not choriocarcinoma (Figure S2).…”
Section: Discussionmentioning
confidence: 53%